Live Imaging of Innate and Adaptive Immune Responses in the Liver - Li, Lu; Zeng, Zhutian (Frontiers in Immunology, 2020)
Immune response in the liver is determined by the spatial organization and cellular dynamics of hepatic immune cells. The liver vasculature accommodates abundant tissue-resident innate immune cells, such as Kupffer cells, natural killer cells, and natural killer T cells, to ensure efficient intravascular immunosurveillance. The fenestrated sinusoids also allow direct contact between circulating T cells and non-canonical antigen-presenting cells, such as hepatocytes, to instruct adaptive immune responses. Distinct cellular behaviors are exploited by liver immune cells to exert proper functions. Intravital imaging enables real-time visualization of individual immune cell in living animals, representing a powerful tool in dissecting the spatiotemporal features of intrahepatic immune cells during steady state and liver diseases. This review summarizes current advances in liver immunology prompted by in vivo imaging, with a particular focus on liver-resident innate immune cells and hepatic T cells.